KRAS, NRAS, and BRAF Hot-Spot Mutations in Relation to Sidedness of Primary Colorectal Cancer: A Retrospective Cohort Study - Omer Abdelgadir; Yong-Fang Kuo; Anthony O. Okorodudu; M. Firoze Khan; Yu-Wei Cheng; Jianli Dong (Diagnostics)
Background/Objective: Studies have shown an association between colorectal cancer (CRC) sidedness and gene mutations that may affect CRC clinical behavior. This study examined the association between specific KRAS, NRAS, and BRAF hot-spot mutations and primary CRC sidedness. Methods: We performed a retrospective cohort analysis of 722 patients diagnosed with primary CRC and tested for KRAS, NRAS, and BRAF hot-spot mutations at the University of Texas Medical Branch (UTMB) from January 2016 through July 2023. Multivariable logistic regressions analyses were conducted. Results:KRAS, NRAS, and BRAF hot-spot mutations rates were 37.8%, 4.6%, and 6.1%, respectively. Right-sided primary CRC had the highest prevalence of mutated tumors (64%). KRAS and BRAF hot-spot mutations were significantly different according to tumor sidedness. KRAS p.Gly12Asp, p.Gly12Val, and p.Gly13Asp showed a significantly increased likelihood of right-sided primary CRC compared to KRAS wildtype, 128%, 134%, and 221% higher, respectively. Conversely, KRAS p.Gly12Val and p.Gly13Asp mutations were associated with decreased likelihood of rectal cancer (53% lower) and left-sided tumors (56% lower), respectively. BRAF p.Val600Glu mutation, as opposed to BRAF wildtype, was associated with a 278% higher likelihood of right-sided CRC. No significant associations were observed between NRAS mutations and primary CRC sidedness. Conclusions: In primary CRC, specific mutations in KRAS (p.Gly12Asp, p.Gly12Val, and p.Gly13Asp) and BRAF p.Val600Glu were associated with increased likelihood of right-sided tumors. KRAS p.Gly12Val and p.Gly13Asp mutations were associated with decreased likelihood of rectal cancer and left-sided tumors, respectively. These findings suggest that tumorigenesis and mutational processes differ based on tumor sidedness. Further studies are needed to substantiate these findings.